Diffraction effects incorporated design of a parallax barrier for a high-density multi-view autostereoscopic 3D display - Yoon, Ki-Hyuk; Ju, Heongkyu; Kwon, Hyunkyung; Park, Inkyu; Kim, Sung-Kyu (OPTICAL SOC AMER, 2016)
We present optical characteristics of view image provided by a high-density multi-view autostereoscopic 3D display (HD-MVA3D) with a parallax barrier (PB). Diffraction effects that become of great importance in such a display system that uses a PB, are considered in an one-dimensional model of the 3D display, in which the numerical simulation of light from display panel pixels through PB slits to viewing zone is performed. The simulation results are then compared to the corresponding experimental measurements with discussion. We demonstrate that, as a main parameter for view image quality evaluation, the Fresnel number can be used to determine the PB slit aperture for the best performance of the display system. It is revealed that a set of the display parameters, which gives the Fresnel number of similar to 0.7 offers maximized brightness of the view images while that corresponding to the Fresnel number of 0.4 similar to 0.5 offers minimized image crosstalk. The compromise between the brightness and crosstalk enables optimization of the relative magnitude of the brightness to the crosstalk and lead to the choice of display parameter set for the HD-MVA3D with a PB, which satisfies the condition where the Fresnel number lies between 0.4 and 0.7. (C) 2016 Optical Society of America
Keywords: VIEWING DISTANCE; IMAGES; TECHNOLOGIES